Blockchain technology impact HR hiring and off-boarding practices in the Telco sector in Hong Kong - Candice, 1. Candy So Suk Yi (Candice); Yung, Eric; Lee, Dr. Samuel; Fong, Dr. Christopher; Tripathi, Shilpi (International Journal of Scientific Research and Management (IJSRM), 2020)
A Deloitte (2016) survey report states that blockchain technology can have an impact on the telecommunications industry in preventing fraud, identifying as-a-service and data management, 5G enabling, and IoT connectivity. For example, fraud costs more than USD 38 billion a year. In a panel of industry experts, Carrier Industry is looking for ways to cut costs, boost revenues, and market segments through blockchain technology (Total Telecom, 2018). Blockchain is treated as a breakthrough technology for managing the operation of telecommunications such as identity management, smart contracts, payments and transactions, reporting and analysis, network management, billing / OSS, etc.  A statistical analysis shows that blockchain in telecommunications and postal services in 2017 amounted to more than USD 39 million and is expected to achieve an estimate of more than USD 641 million by 2023-end, suggesting powerful market growth over the next few years (Market Research Future Report, 2018). Since carriers apply telecom standards to run its business and operations, and thus blockchain technology, a high secure of distributed ledger and trust processes to solve the high traffics.   According to a survey by IBM Institute for Business Value (2018), it states that 36 percent of Communication Service Providers (CSP) are already considering or actively engaged with blockchain, 41 percent of CSP may support their strategy by assuring data management, and 46 percent of CSP are already exploring or engaging with blockchain and already invested in it to develop new business models. Carriers in telecommunications Industry Hong Kong are mainly private-owned, and thus they must follow the Telecommunication Ordinance (Cap. 106) governed by Office of the Communications Authority (OFCA) of HKSAR. Telecommunications services such as fixed-line, internet broadband and mobile service support business and residential customers.    Hong Kong Telecom (HKT), Hutchison Telecommunications Hong Kong Holdings Ltd (HTHK) and Hong Kong Broadband Network Limited (HKBN) are selected by this study as a number of operators (fixed-line and broadband, mobile, or a mix of both fixed-line, broadband and mobile).  HKT (Stock Code: SEHK: 6823), is the major operator to meet the needs of public, local and international businesses with a wide range of services such as local telephony, local data and broadband, international communications, mobile service and enterprise solutions. HKT employs approximately 17,400 staff, the headquarters are located in Hong Kong, and telecommunications network covers more than 3,000 cities and 140 countries (HKT, 2019) Hutchison Telecommunications Holdings Hong Kong Limited (Stock Code: SEHK215), conglomerate of CK Hutchison Holdings, is the leading operator provides mobile service in Hong Kong and Macau.  HTHK employs 1,180 staff and the headquarters are located in Hong Kong (HTHK, 2019). Hong Kong Broadband Network, Stock Code: SEHK: 1310), is the foremost operator provides broadband service to commerce and residential customers. HKBN is an aggressive operator with merger and acquisition with New World Telecommunications in February 2016 and WTT Holding Ltd in February 2019. HKBN employs approximately 3,000 staff, and the headquarters are located in Hong Kong (HKBN, 2019).  An example of two dominating carrier representatives, Marc Halbfinger, Chief Executive Officer of PCCW Global (subsidiary of HKT) and the Chairman of the GLF, and Andrew Kwok, CEO of Hutchison Global Telecommunications (ex-mega conglomerate of CK Hutchison Holdings sold to Asia Cube Global in Jul 2017) partnering with Colt Technologies Service to conduct trial blockchain technology to re-shape business practices (Colt Technology News, 2018). Other example of blockchain, HKT and PCCW obtained a virtual banking license in early 2019 to expand finance business (South China Morning Post, 2019). Given examples of operators actively study on blockchain technology to its core business and the role of blockchain plays a tremendous role in telecommunications landscape.  The research paper is focussed on blockchain/blockchain technology impact to Human Resources hiring and off-boarding practices in telecommunications sector in Hong Kong.